Booster juice – big shoes to fill. Issue 3 (12th September 2016) - Fergus, Andrew; Bell, Tony
Abstract : Synopsis: Ian Henson was about to take the biggest financial risk of his life. He had just agreed to purchase three Booster Juice franchise stores in Kamloops, British Columbia, Canada. Henson knew that transitioning leadership at companies was a difficult task, and he was aware that he was replacing a popular leader: Natalie Peace. Compounding the challenge ahead of Henson were two major hurdles, the first was demographic in nature: Booster Juice's employee group was young (on average below 20 years old) and many adored Peace, he was certain that whoever replaced her would have a difficult transition. The second challenge was managing change: Henson needed to cut costs. Peace had several generous policies that Henson needed to consider altering or removing, a potentially unpopular task. Initially, this case puts students in Henson's shoes: How should he handle the specific aspects of this leadership transition? It allows professors to examine the broader issue of managing a change process. Research methodology: Data for the case were collected from various sources. Public records, historical documents, and media reports were the main source for general background information and context. Primary data were collected through a series of interviews with the present and past owners of the Booster Juice franchises discussed. Relevant courses and levels: This case was developed for use in an undergraduate management course or where change management and leadership are specific modules, an organization behavior class is a good example of where the case should fit. The objective of the case is to illustrate the challenges that resulted from a change in leadership and examine how to manage the change process. The thought-provoking element in this case is the leaders involved have very different leadership styles. The authors anticipate this case would be one used early in the course, as it is concise and straightforward to read, and clearly illustrates the issues to be examined. It provides an effective tool through which to introduce students to change management and styles of leadership. The added value is that the case is based on a company built by an undergraduate student and thus students tend to be very interested in the business itself. Theoretical bases: The main theoretical base for the case is based on change management and exemplary leadership. To facilitate this the authors use Kurt Lewin's models of change, Kotter's eight step process, specifically referring to Kotter (1995). The authors then use Kouzes & Psoner five practices of exemplary leadership, referring to Kouzes, and Posner (2003). The authors specifically reference Northouse (2010).